The Politeness Strategy of Directive Utterances Used by the Students in Sahid Tourism Institute of Surakarta:A Pragmatic Perspective - Yusitasari, Ita Auliya (2017)
The current study is aimed to investigate the linguistic type and politeness strategy used by the second semester students of Sahid Tourism Institute of Surakarta. The study used descriptive qualitative research, which include fifteen students in second semester at Sahid Tourism Institute of Surakarta. The data are collected by using Discourse Completing Task (DCT). The data are analyzed by using the theory of liguistic types by Marcela Frank, and politeness strategy by Brown and Levinson. Based on the analysis of written responses to DCT, the study found that the students were able to produce 3 types of linguistic: declaratives, imperatives, and interrogatives. However, this study also found small percentage of students who wrote inappropriate response that cannot be classified into any linguistic types. In terms of politeness strategy, the result of this study indicated the students were able to produce 3 types of politeness strategy: bald on record, positive politeness, and negative politeness. Interestingly, this study also found small percentage of students who wrote inappropriate response that cannot be classified into any politeness strategy. Keyword: linguistic types, politeness strategy.